Credit risk model of commercial banks. - Lim, Serena Xiu Ling. (2009)
In year 2008, the number of bank defaults in the U.S was 25, the highest recorded in nine years. In just the first two months of year 2009, the number of bank defaults was 16. The detrimental and domino-like repercussions of these defaults cannot be undermined. Common credit risk models to predict default probability are mainly tailored towards the manufacturing industry. A test of the more commonly used Edward I. Altman’s Z-score model on the banking industry gave faulty results, and further proved the unsuitability of these models for the banking industry. There is thus a need to develop a model that can accurately predict bank defaults in a stipulated time period, which was chosen as five years.